2022
DOI: 10.7717/peerj.14107
|View full text |Cite
|
Sign up to set email alerts
|

Mutualist- and antagonist-mediated selection contribute to trait diversification of flowers

Abstract: Flowers are generally short-lived, and they all face a multidimensional challenge because they have to attract mutualists, compel them to vector pollen with minimal investment in rewards, and repel floral enemies during this short time window. Their displays are under complex selection, either consistent or conflicting, to maximize reproductive fitness under heterogeneous environments. The phenological or morphological mismatches between flowers and visitors will influence interspecific competition, resource a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 146 publications
0
1
0
Order By: Relevance
“…The rst studies shedding light on the effects of herbivory/ orivory on oral scents and pollinator behavior, were published less than two decades ago. reviewed by 137,[200][201][202][203][204] Meanwhile, there are some studies available that link herbivory on leaves and owers to oral chemistry and pollinator attraction. They have found that herbivory/orivory oen, but not always, 169,205 has effects on oral scent emissions, 177,206 and that different herbivores can have different effects on oral scent emissions.…”
Section: Herbivoresmentioning
confidence: 99%
“…The rst studies shedding light on the effects of herbivory/ orivory on oral scents and pollinator behavior, were published less than two decades ago. reviewed by 137,[200][201][202][203][204] Meanwhile, there are some studies available that link herbivory on leaves and owers to oral chemistry and pollinator attraction. They have found that herbivory/orivory oen, but not always, 169,205 has effects on oral scent emissions, 177,206 and that different herbivores can have different effects on oral scent emissions.…”
Section: Herbivoresmentioning
confidence: 99%